Dhuafa Mart's Strategy in Popularizing the Concept of Sharia Buying and Selling - Saru Reza; Zubaidah Assyifa; Wahyu Febri Ramadhan Sudirman; Binda Rahma Cahyani; Sela Hermawanti (Global Sustainability Research Institute, 2025)
This community service was carried out at Dhuafa Mart Air Tiris with the main target being consumers who shop there. This activity aims to improve consumer understanding of the concept of sharia-based buying and selling. The method used in this activity is an interactive discussion, where consumers are explained the principles of sharia buying and selling, followed by a question and answer session to deepen their understanding. The activity results show that consumers who participate in this program gain increased knowledge about transactions that follow Islamic sharia principles. Furthermore, the delivery of the material is expected to encourage consumers to implement sharia buying and selling practices in their daily economic activities. By implementing sharia principles in transactions, it is hoped that a fairer, more transparent trading environment will be created, and will provide benefits for consumers and the management of Dhuafa Mart.